2018
DOI: 10.17219/acem/74389
|View full text |Cite
|
Sign up to set email alerts
|

Elevated beta-thromboglobulin and mean platelet volume levels may show persistent platelet activation in systemic lupus erythematosus patients

Abstract: Elevated beta-thromboglobulin levels in systemic lupus erythematosus patients may be associated with platelet activation in the early stages of disease, whereas lower mean platelet volume levels in the same population may be due to the effects of hydroxychloroquine and the inactivity of SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In all patients who were in SLE remission, the CRP, leukocyte, and complement levels were normal. The authors suggested that hydroxychloroquine therapy contributed to the lower MPV values[29]. The lower MPV values obtained in the study group were probably associated with higher disease activity.…”
mentioning
confidence: 80%
“…In all patients who were in SLE remission, the CRP, leukocyte, and complement levels were normal. The authors suggested that hydroxychloroquine therapy contributed to the lower MPV values[29]. The lower MPV values obtained in the study group were probably associated with higher disease activity.…”
mentioning
confidence: 80%